2014
DOI: 10.7314/apjcp.2014.15.4.1633
|View full text |Cite
|
Sign up to set email alerts
|

Oral Extranodal Non Hodgkin's Lymphoma: Series of Forty Two Cases in Malaysia

Abstract: Background: Lymphoma is a malignant neoplasm of lymphoid tissue classified into Hodgkin's and nonHodgkin's types. It mostly affects lymph nodes although a considerable proportion of Non-Hodgkin's cases occur in extranodal sites. Materials and Methods: Selected cases diagnosed as non-Hodgkin's lymphoma (NHL) during the period of 1980 to 2012 were retrieved from the archives of the Oral Pathology Diagnostic Laboratory, Faculty of Dentistry, University of Malaya. The sections from the formalin-fixed paraffin embe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 30 publications
0
21
1
Order By: Relevance
“…The 16 case series [5, 2943] included in the SR are shown in Table 1. Two case series were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…The 16 case series [5, 2943] included in the SR are shown in Table 1. Two case series were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…which confirmed the B-cell lymphoma subtype. The expression of CD20 is the most frequent in oral extranodal non-Hodgkin's lymphoma [28]. The endoscopy showed the presence of erythematous gastritis.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ramanathan et al reported an analysis of oral extronodal NHL cases (Ramanathan et al, 2014). In their paper, the authors selected forty two patients diagnosed with extranodal oral cavity NHL.…”
Section: The Imaging Features Of Aids-related Non-hodgkin's Lymphomamentioning
confidence: 99%